SobreVidas Platform – “Oral Cancer”: A Technological Solution for Tracking and Continuous Monitoring in Primary Health Care - Pedrosa, Leandro; Costa, Luiza de Oliveira; Siqueira, Nara Rúbia Pereira de; Peraro, Thiago de Jesus; Reis, Gabriel Freitas dos; Viglio, Stephano Soares; Rodrigues, Pedro Augusto; Jawabri, Omar Al; Morais, Carlos Henrique Alves; Espíndola, Vinicius Pereira; Castilho, Suse Barbosa; Ribeiro-Rotta, Rejane Faria; et al. (Companion Proceedings of the Brazilian Symposium on Computing Applied to Healthcare (SBCAS); 2025: Companion Proceedings of the 25th Brazilian Symposium on Computing Applied to Health, 2025)
Oral cancer has a high mortality rate, especially when diagnosed at advanced stages. This paper presents the SobreVidas – “Oral Cancer” Platform, an artificial intelligence-based solution designed to support the screening and monitoring of at-risk populations in Primary Health Care. By applying agile methods for software management and development, a microservices architecture, authentication via Keycloak, large language models, and Retrieval-Augmented Generation techniques, the platform is secure, scalable, and focused on clinical decision support. The results indicate technical feasibility and strong potential to enhance early detection and the follow-up of individuals at risk.